Event-triggered Scheduling for Infrastructure-supported Collaborative Vehicle Control*. Issue 22 (2016) - Molin, Adam; Esen, Hasan; Johansson, Karl H.
Abstract: This paper investigates the design of event-triggered scheduling and medium access control for the real-time coordination of multiple vehicles through an infrastructure node. The key motivation of our proposed event-triggered mechanism is to concurrently address safety aspects of the vehicle control and the efficient usage of network resources of the vehicle-to-infrastructure (V2I) protocol. While the real-time guarantees needed for safety are achieved by a novel coordination scheme in the medium access layer, the event-triggered mechanism improves the real-time performance of the control task. The coordination scheme enabled through the topology of the V2I network limits the number of successive data dropouts and we prove stability of the estimator at the infrastructure that monitors the state of the vehicle group. Numerical studies on a platooning case study validate our theoretical results.